Grandparental Childcare for Biological, Adopted, and Step-Offspring: Findings From Cross-National Surveys - Tanskanen A.O.; Danielsbacka M.; Rotkirch A. (SAGE Publications Inc., 2022)
Based on kin selection theory, amounts of grandparental investment should reflect the probability to share common genes with offspring. Adoption may represent a special case, however, yet grandparental investment in adopted children has previously been both theoretically misconstrued and little investigated. Here, we study for the first time how grandparental childcare provision is distributed between biological, adopted, and step-offspring. Using Generations and Gender Surveys (n = 15,168 adult child–grandmother and 12,193 adult child–grandfather dyads) and the Survey of Health, Ageing, and Retirement in Europe (n = 17,233 grandmother–adult child and 13,000 grandfather–adult child dyads), we find that grandparents were less likely to provide care to stepchildren than to adopted and biological children, but no difference between adopted and biological children. These findings were present in both data sets and for both grandmothers and grandfathers, after several potentially confounding factors were taken into account. The stepchild disadvantage is in line with kin selection theory. The congruent amounts of care provided to adopted and biological children may reflect similar levels of adult–child attachment, selection effects, and greater need in adoptive families, as well as some degree of genetical relatedness in the case of kin adoption. The study provides new evidence of biased kin investments in contemporary societies and stresses the importance of psychological motivation and attachment in evolutionary studies of kin investment.